Introducing New Testament interpretation - McKnight, Scot (Grand rapids, MI Baker, 1989)
Includes bibliographical references.
Contributors include Darrell L. Bock, Draig A. Evans, Thomas E. Schmidt, etc.
Keywords: Bible. N.T. -- criticism, interpretation, etc